PENERAPA MATEMATIKA PADA ILMU EKONOMI: FUNGSI LINIER - Januarta, Alfino Ardy; Naura Zahra , Calysta Lintang; Hariyanto, Eky Syaputri; Cindy , Putri Mai; Safrilian Alihuddin, Muhammad; Amara Faradiva, Melisa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Economic mathematics plays an important role in analyzing various economic phenomena, one of which is through the concept of linear functions. A linear function is a simple function whose equation form consists of coefficients and constants (parameters) and consists of several independent variables and independent variables of degree or rank one. The purpose of this research is to help us understand more about linear functions in economic mathematics. This research uses a description research method with a literature review approach, namely data collection carried out by collecting valid data sources from, scientific journals, and related articles. The results of this study indicate about student problem solving in linear function material. Economic mathematics helps analyze economic problems using mathematical tools, including linear functions. These functions are simple but very useful in describing the direct relationship between variables that affect economic decisions, such as production and consumption. By using models such as linear functions, economists can analyze such as production, consumption, and distribution of goods and services, to solve complex economic problems.